PREDICTION OF THE EFFECT OF SINGLE NUCLEOTIDE POLYMORPHISMS (SNPS) IN THE CYP2C9 ON WARFARIN METABOLISM BY IN SILICO STUDY - PUTRIANA, NORISCA ALIZA; RUSDIANA, TAOFIK; ROSTINAWATI, TINA; AKBAR, MOHAMMAD RIZKI; MEGANTARA, SANDRA; HIDAYANTI, SABRANAH (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to predict the effect of SNPs CYP2C9 s on the metabolic activity of S-warfarin in the body. Methods: Molecular modeling was performed to obtain SNPs CYP2C9 and molecular docking was performed to predict the effect of SNPs CYP2C9 on the metabolic activity of S-warfarin. Results: The results showed that wild-type CYP2C9 had the strongest binding affinity (∆G: -9.76 kcal/mol), indicating that wild-type CYP2C9 had the best metabolic activity compared to SNPs CYP2C9. There was a decrease in hydrogen bond formation in SNPs CYP2C9 and an increase in the distance between C7 S-warfarin and Fe-Heme in CYP2C9 SNPs when compared to wild-type CYP2C9 Conclusion: The decrease in binding affinity, decrease in hydrogen bond formation, and an increase in the distance between C7 S-warfarin and Fe-Heme on SNPs CYP2C9 indicated that SNPs CYP2C9 had decreased metabolic activity against S-warfarin which led to an increased risk of bleeding.